Hydrogeological Characterization of Phuket Aquifer System with Reference to Groundwater Development of Phuket, Thailand - Sam OI KONG (Prince of Songkla University, 2018)
Thesis (M.Sc., Earth System Science)--Prince of Songkla University, 2017